ANALISIS YURIDIS IMPLEMENTASI MUDHARABAH PADA BANK SYARIAH DI KOTA MAKASSAR : JURIDICAL ANALYSIS OF MUDHARABAH IMPLEMENTATION IN SHARIA BANK IN MAKASSAR CITY - Elnizar, Muh. Reza; A. Hasan, Yulia; Santing, Waspada (Clavia, 2021)
This study aims to find out the implementation of Akad Mudharabah and to find out what factor’s influence Mudharabah in Sharia Banks in Makassar City. This research was conducted in BPRS Dana Moneter, BNI Syariah and BTN Syariah using empirical law research type, the approach is carried out by studying the actual law through interviews and fact-based documentation. The results showed that the implementation of the Mudharabah agreement at Sharia Banks in Makassar City showed that the implementation of the Mudharabah agreement in the Monetary Fund BPRS, BNI Syariah and BTN Syariah is still completely un implemented due to the many opinions of the Customer such as the absence of an agreement at the beginning by both parties, the determination of the Ratio determined by the Bank itself and other matters. As well as the factors that influence the implementation of Mudharabah, namely NPF (bank health), FDR (Financing ratio), inflation (price increase) and BOPO (Oprasional Burden on Oprasional Income) all of these factors are in keeping with the bank's performance in implementing the Mudharabah agreement. therefore, each agency is expected to increase product recognition activities and maintain its bank operations.